Pakistan’s Green Urbanization in the Perspective of Ecological Civilization - Muhammad Sabil FAROOQ; Nazia FEROZE; Tongshun CHENG; Faisal FEROZE (Chinese Journal of Urban and Environmental Studies, 2024)
Within the context of ecological civilization, this study examines Pakistan’s path toward green urbanization. This study’s main driving force is Pakistan’s rapidly urbanizing landscape, which makes it imperative to address environmental degradation and advance sustainable development. A paradigm change towards green urbanization is required because of the multiple environmental difficulties brought about by urbanization in Pakistan, such as pollution, resource depletion, and habitat loss. This study examines the current status of green urbanization in Pakistan through a thorough analysis using a mixed-methods methodology that combines quantitative data analysis with qualitative evaluations. The findings show that, although there are regional variations in the extent of implementation, there is a growing consciousness of and desire to implement eco-friendly policies and practices within urban areas. Goals for green urbanization are seriously hampered by issues including poor infrastructure, scarce resources, and institutional capacity limitations. However, there are encouraging indications of development such as programs supporting green building techniques, sustainable transportation, and renewable energy. Beyond the confines of academia, the research has implications that teach stakeholders, legislators, and urban planners about the necessity of incorporating ecological principles into urban development initiatives. Pakistan can reduce environmental risks, increase climate change resistance, and promote inclusive, sustainable cities for future generations by adopting green urbanization.